Analysis of Human Resource Requirements After The Implementation of Electronic Medical Records at RSI Yarsis - Nopita Cahyaningrum; Khoirul Mustofa; Lintang Dwi Elyan; Rika Andriani (Jurnal Infokes, 2026)
The implementation of Electronic Medical Records (EMR) at Yarsis Islamic Hospital Surakarta has changed the work system and workflow of outpatient registration officers. This different workflow will undoubtedly alter existing human resource requirements, impacting the productivity of registration staff. This study aims to analyze human resource (HR) requirements in the outpatient registration unit after the implementation of EMR using the Health Workload Analysis (ABK-Kes) method. This study employed a descriptive qualitative approach with a cross-sectional design. Data were collected through observation and interviews with four outpatient registration officers. Data processing included collecting, editing, tabulation, and data presentation. The analysis of human resource requirements was conducted using the Health Workload Analysis (ABK-Kes) method, which includes calculating available working time (WKT), determining workload components and standard time, calculating workload standards (SBK), supporting task standards (STP), and supporting task factors (FTP). The data were analyzed descriptively. The results showed that the required number of human resources was one officer for the morning shift and two officers for the afternoon shift. Currently, there are four registration officers employed at the hospital. It can be concluded that there is an excess of one registration officer. This study recommends regular evaluations of HR needs and workloads, particularly during increases in patient visits or changes in service systems, to ensure appropriate workforce allocation. Improving staff competencies and educational qualifications in accordance with applicable regulations is also necessary to support sustainable service quality